Π–π Stacking Induced Enhanced Molecular Solubilization, Singlet Oxygen Production, and Retention of a Photosensitizer Loaded in Thermosensitive Polymeric Micelles. Issue 12 (11th November 2014) - Shi, Yang; Elkhabaz, Ahmed; Yousef Yengej, Fjodor A.; van den Dikkenberg, Joep; Hennink, Wim E.; van Nostrum, Cornelus F.
<x xml:space="preserve">Abstract</x> Cancer photodynamic therapy (PDT) by photosensitizers (PS)‐loaded polymeric micelles (PM) is hampered by the tendency of PS to aggregate in PM and/or by premature release of PS in the blood circulation. In the present study, aromatic thermosensitive PM, characterized by π–π stacking interaction, are used to encapsulate an axially solketal‐substituted silicon phthalocyanine (Si(sol)2Pc) with enhanced loading capacity, smaller size, and significantly improved retention of Si(sol)2Pc compared with systems based on thermosensitive PM lacking aromatic groups. Interestingly, Si(sol)2Pc is much less prone to aggregation in the aromatic PM, i.e., the amount of Si(sol)2Pc that could be encapsulated without aggregation is 330 times higher in the aromatic PM than in the nonaromatic PM. Furthermore, Si(sol)2Pc in the aromatic PM in a molecularly dissolved (non‐aggregated) form displays three times more efficient singlet oxygen production than Si(sol)2Pc aggregated in the non‐aromatic PM. As a result, the photocytotoxicity of Si(sol)2Pc‐loaded aromatic PM to B16F10 cells is increased, compared with that of the non‐aromatic PM, while no significant cytotoxicity is observed in the dark. Fluorescence‐activated cell sorting (FACS) and confocal laser scanning microscopy (CLSM) analysis shows cell uptake of Si(sol)2Pc loaded in the aromatic PM, and the Si(sol)2Pc is taken up by the cells together with the micelles. The efficient singlet oxygen production of Si(sol)2Pc dissolved in the aromatic PM makes it an interesting formulation for cancer PDT.